2009
DOI: 10.1590/s1413-70542009000300022
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de casca de arroz e esterco bovino como substrato Eisenia fetida Savigny (1826)

Abstract: RESUMOA utilização de minhocas, principalmente para a alimentação animal, vem sendo adotada e estudada, pois esses organismos apresentam em sua constituição vitaminas e aminoácidos. Entre os materiais possíveis de serem utilizados na minhocultura, atualmente incentiva-se o aproveitamento de resíduos agroindustriais de alta disponibilidade, como a casca de arroz no Rio Grande do Sul. Objetivou-se, neste trabalho, avaliar a eficiência de substratos à base de casca de arroz e esterco bovino na multiplicação e pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
5
0
7
Order By: Relevance
“…The species E. andrei and E. foetida have similar characteristics and behavior (Atiyeh et al, 2000), the results obtained in this work regarding the multiplication of the E. foetida species were compared with results presented in the literature for both species (Antoniolli et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The species E. andrei and E. foetida have similar characteristics and behavior (Atiyeh et al, 2000), the results obtained in this work regarding the multiplication of the E. foetida species were compared with results presented in the literature for both species (Antoniolli et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…For the determination of the multiplication index of earthworms, was used the formula IM = Pf / Pi, where Pf = final population of worms and Pi = initial population of worms, corresponding to the number of inoculated matrices (Antoniolli et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Such reduction is caused by microorganisms or by gas exchange with the atmosphere. Ammonia may be The multiplication index is the parameter used to assess the reproductive capacity of matrices in a given environment (ANTONIOLLI et al, 2009). The species E. andrei and E. fetida present similar features and behavior (ATIYEH et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Results recorded for the first 3 doses (Figure 2A) used in the current study were also higher than those found by Pereira et al (2005), who used pure cattle manure and recorded multiplication index 2.1. Antoniolli et al (2009) conducted a study with E. fetida and used mixtures comprising cattle manure and rice husk in the initial inoculation of 6 matrices in 4 L manure; they found higher multiplication index (8.5) and smaller numbers of cocoons (57) in the same period. Schiavon et al (2007) conducted an experiment of similar nature and found a large number of cocoons in treatment using pure cattle manure; they inoculated 10 earthworms belonging to species E. fetida in 300 g substrate and collected 138 cocoons 28 days after inoculation, fact that showed E. fetida reproductive efficiency in this material.…”
Section: Resultsmentioning
confidence: 99%
“…Diferentes resíduos orgânicos podem ser utilizados com sucesso no processo de vermicompostagem. Devido a grande disponibilidade, existem diversos trabalhos com o esterco de bovinos (ANTONIOLLI et al, 2009;STEFFEN et al, 2010;ECKHARDT, 2011;DOMÍNGUEZ;GÓMEZ-BRANDÓN, 2013), no entanto, ainda há poucas pesquisas com esterco de coelhos, ovinos e conteúdo do rúmen de bovinos.…”
Section: Introductionunclassified